Experimental study of Circular Short Columns made from Reactive Powder Concrete - Asmaa Ali Ahmad; Faidhi Abdul-Rahman Alkhazraji; Sarah Mohammed Omar (Engineering and Technology Journal, 2016)
This research studies the behavior of reactive powder concrete (RPC) circular short columns with and without steel fibers of different types, as well as change of the reinforcement kinds of lateral (hoops and spiral) and the spacing between them. The experimental work consist study of fifteen short column specimens having an overall height of 1 m with circular cross-section of 150 mm diameter are loaded at ends with concentric loads. Six of the specimens are cast with the inclusion of steel fibers with aspect ratio of 75(group 1), and six of other specimens are cast with the inclusion of steel fibers with aspect ratio of 100 (group 2),and the other three specimens is without steel fibers, with hybrid steel fibers and high strength concrete. The concrete mix of fiber-reinforced samples contains 1% by volume of steel fibers of variable reinforcement longitudinal and lateral (hoops and spiral reinforcement). Experimental data for strength, failure mode, lateral, and the ductility were obtained for each test. The work concluded that the using of steel fibers in RPC was an effective way to prevent spalling of the concrete cover and increase the ductility and the using of high ratio of longitudinal reinforcement delays the pickling of the columns and increase strength. The ultimate load capacity of RPC columns of spiral lateral reinforcement is greater than the load of RPC columns of tied lateral reinforcement by about 1.25 to 1.35 times for the two groups.